Antidiabetic properties of phytosynthesized gold nanoparticles (AuNPs) from Datura stramonium seed. Issue 1 (March 2020) - Oladipo, I C; Lateef, A; Azeez, M A; Asafa, T B; Yekeen, T A; Ogunsona, S B; Irshad, H M; Abbas, S H
Abstract: The gold nanoparticles synthesized from Datura stramonium seed was investigated for its antidiabetic properties in the present study. A total number of 42 healthy male albino rats with body weight ranges of 150±20 g were purchased and 7 days acclimatization was carried out after which they were randomly divided into 7 groups (A-G) of 6 animals each. Group A, the control was not induced while the other six groups (B-G) were induced with 150 mg/kg of alloxan by intraperitoneal administration. After 72 h, measurement of the tail vein blood glucose was done to confirm hyperglycemia. Experimental rats with fasting glucose levels (5.6-6.9 mmol/l) were considered diabetic. Group B received no treatment, Group C received 1000 μg/kg of Datura stramonium seed extract, Group D received 500 μg/ml of synthesized AuNPs, Group E received 750 μg/ml of synthesized AuNPs, Group F received 1000 μg/ml of synthesized AuNPs and Group G received 1000 μg/ml of standard drug (glibenclamide). This treatment was administered every day for 21 days. The result showed that the weight of the rats reduced after diabetes induction but after 21 days of treatment, the weight of the treated groups increased when compared to the untreated group. Furthermore, it was observed that after the treatment with 500 and 750 μg/ml AuNPs, the blood sugar was down regulated unlike the untreated groups. Due to the alloxan induction, there were increases in aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), urea and creatinine levels in the serum of experimental rats, which were significantly reduced after the treatment with Datura stramonium seed extract and the synthesized nanoparticles at 500, 750 and 1000 μg/ml. The histopathology of the pancreas of alloxan induced rats showed severe fibrotic interlobular connective tissues with severely diffused, degenerated, and necrotized Islets of langerhans which were also normalized by treatments with AuNPs. It was confirmed in this research that AuNPs could be embedded in drugs or folk medicine aimed at reducing blood sugar levels.